Optimization of Liquid Oxygen Distribution Routes in Demand Conditions at Risk of Change After the Fleet Departs for the Agents - Sinaga, Tuti Sarma; Pandapotan, Andreas (Jurnal Rekayasa Sistem & Industri, 2024)
This study addresses vehicle routing to distribute liquid oxygen products from the factory to the agent by considering the risk of changes in liquid oxygen demand when the vehicle leaves the factory. Handling liquid oxygen inventory requires strict service, large storage areas and high storage costs. The uncertainty of liquid oxygen demand at the consumer level and inventory handling make agents change demand suddenly. This condition causes the quantity transferred to the agent not to match the amount of liquid oxygen transported by the fleet from the factory. If the change in demand decreases, the fleet must return the remaining liquid oxygen to the factory. Still, if the change increases, it will affect the vehicle's ability to meet the liquid quantity requested by the next agent. Furthermore, a vehicle routing model is developed that considers the possibility of changes in demand after the vehicle departs from the factory. The search for the optimal route solution for this model uses a guided local search algorithm. The study results showed an increase in vehicle transfer quantity of 4.23% from the previous route.